Qualitative versus Quantitative Research - Oflazoglu, Sonyel (IntechOpen, 2017)
The objective of this book is to fill the gap combining several studies from qualitative and quantitative research methods. The various chapters presented here follow several approaches that researchers explore in different context. This book intends to contribute to better understanding of the application areas of qualitative research method and to show how these business practices in social sciences can stimulate in various areas.